Attachment styles, memories of parental rearing and therapeutic bond: A study with eating disordered patients, their parents and therapists - Tereno, Susana (2008)
Patients diagnosed with anorexia nervosa (n = 30) and bulimia nervosa (n = 27), their parents and therapists were recruited for this study aimed at examining differences between clinical groups and a control group (n = 35) in terms of attachment styles and perceptions of memories of parental rearing. Within the clinical groups, relations among these variables and therapeutic bond were explored. In addition, parents' and their daughters' attachment styles were compared. The results showed differences between clinical and control groups: the daughters in the control group reported lower levels of attachment anxiety compared to those of the clinical groups; their mothers exhibited higher security than mothers of anorectic patients and lower avoidance than mothers of bulimic patients. For the anorectic group, therapeutic bond was associated to higher father's emotional support and lower rejection; in the bulimic group, therapeutic bond was related to higher maternal emotional support and lower rejection as well as to lower paternal overprotection.